Monetary Transmission in an Emerging Targeter : The Case of Brazil - Pagan, A. R. (IMF Working Papers; Working Paper, 2008)
This paper lays out a structural model that incorporates key features of monetary transmission in typical emerging-market economies, including a bank-credit channel and the role of external debt accumulation on country risk premia and exchange rate dynamics. We use an SVAR representation of the model to study the monetary transmission in Brazil. We find that interest rate changes have swifter effects on output and inflation compared to advanced economies and that exchange rate dynamics plays a key role in this connection. Importantly, the response of inflation to monetary policy shocks has grown stronger and the output-inflation tradeoff improved since the introduction of inflation targeting.